Determinación de compuestos polifenólicos, terpénicos y perfil cromatográfico en distintos sistemas de Annona cherimola Mill. "chirimoya" (Annonaceae) - Haag, Griselda Octavia (2017)
The objective of the present work was to extract, isolate, characterize and identify, from the leaves of A. cherimola, polyphenols and triterpenes steroids that could support their uses in traditional medicine; As well as to establish chromatographic profiles for the extracts of this species in order to establish the identity and the quality control of the same. The results found allow to determine the presence of flavonoids and other polyphenolic compounds in the methanolic extracts n-butanol and aqueous; As well as terpenoids in the chloroform extract. TLC and HPLC-DAD against controls show that flavonoids and polyphenolic compounds correspond to rutin, isoquercetin and caffeic acid; While among the terpenes were ursolic and oleanolic acids. Given the aforementioned antecedents, it is reasonable to argue that traditional uses of cherimoya could be related to the activity and / or synergy of some of the flavonoids and polyphenols (rutin, isoquercetin, caffeic acid) and terpenoids (ursolic and oleanolic acids) found .